Entrepreneurship the Disney way - Goldsby, Michael G.; Mathews, Robert (Routledge, 2019)
The authors' interviews with high-level executives provides the reader with a rare inside look into the way his company functions. Disney fans, executives, and students of entrepreneurship, innovation, and leadership will find it a delightful and informing read